Jakarta's great land transformation: Hybrid neoliberalisation and informality. (March 2019) - Herlambang, Suryono; Leitner, Helga; Tjung, Liong Ju; Sheppard, Eric; Anguelov, Dimitar
We analyse dramatic land transformations in the greater Jakarta metropolitan area since 1988: large-scale private-sector development projects in central city and peri-urban locations. These transformations are shaped both by Jakarta's shifting conjunctural positionality within global political economic processes and by Indonesia's hybrid political economy. While influenced by neoliberalisation, Indonesia's political economy is a hybrid formation, in which neoliberalisation coevolves with long-standing, resilient oligarchic power structures and contestations by the urban majority. Three persistent features shape these transformations: the predominance of large Indonesian conglomerates' development arms and stand-alone developers; the shaping role of elite informal networks connecting the development industry with state actors; and steadily increasing foreign involvement and investment in the development industry, accelerating recently. We identify three eras characterised by distinct types of urban transformation. Under autocratic neoliberalising urbanism (1988–1997) peri-urban shopping centre development predominated, with large Indonesian developers taking advantage of close links with the Suharto family. The increased indebtedness of these firms became debilitating after the 1997 Asian Financial Crisis. Thus post-Suharto democratic neoliberalising urbanism (1998–2005) was a period of minimal investment, except for shopping centres in DKI Jakarta facilitating a consumption-led strategy of recovery from 1997, and the active restructuring of elite informality. Rescaled neoliberalising urbanism (2006–present) saw the recovery of major developers, renewed access to finance, including foreign capital, and the construction of ever-more spectacular integrated superblock developments in DKI Jakarta and peri-urban new towns.